PEMANFAATAN BAHAN SEDERHANA SEBAGAI MEDIA PEMBELAJARAN DI TK ISLAM AN-NISA KEPENGHULUAN SUNGAI PINANG KECAMATAN KUBU KABUPATEN ROKAN HILIR - Hasan, Hasan; Novita Sari; Delima Putri (Jurnal Payung Sekaki : Kajian Keislaman, 2026)
Early childhood education is key to developing children's potential. Early childhood education aims to build a strong foundation for children's physical, mental, and social development. To develop this potential, teachers need to be creative in their teaching. One example of this is how teachers are able to create appropriate learning media. This study aims to examine the extent to which teachers can utilize simple materials as learning media at An-Nisa Islamic Kindergarten and to find out why teachers are less interested in utilizing simple materials as media at An-Nisa Kindergarten in Sungai Pinang Village, Kubu District, Rokan Hilir Regency. This study uses a qualitative research method. This study is a population study. The subjects of this study are four teachers at An-Nisa Islamic Kindergarten in Sungai Pinang Village, Kubu District, Rokan Hilir Regency. Data collection was conducted through observation and interviews. Meanwhile, data analysis was performed using qualitative descriptive techniques. The results of this study are as follows: 1. A total of 14 topics (38.88%) of learning were carried out using simple materials as learning media. 2. A total of 22 topics (61.11%) used digital/manufactured media.